1929
DOI: 10.1104/pp.4.2.281
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Flowers

Abstract: This paper is concerned with the opening and closing processes in the flowers of Crocus and Tulipa. As is well known from the work of PFEFFER, the flowers of Crocus and Tulipa are only slightly photonastic. They are, however, extremely thermonastic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

1953
1953
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…The maximum iron capacity measured under the conditions tested was ∼2700. This is significantly less than theoretical value of ∼4500 (30, 31) calculated for mammalian ferritin under the assumption that the crystalline core has a ferrihydrite-like structure (i.e., 5Fe 2 O 3 ‚9H 2 O) (32-34) but significantly greater than the average iron content of BFR cores isolated from nonoverxpressing strains (2). An effective capacity well under 4500 was also recently observed for horse spleen ferritin (35).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The maximum iron capacity measured under the conditions tested was ∼2700. This is significantly less than theoretical value of ∼4500 (30, 31) calculated for mammalian ferritin under the assumption that the crystalline core has a ferrihydrite-like structure (i.e., 5Fe 2 O 3 ‚9H 2 O) (32-34) but significantly greater than the average iron content of BFR cores isolated from nonoverxpressing strains (2). An effective capacity well under 4500 was also recently observed for horse spleen ferritin (35).…”
Section: Discussionmentioning
confidence: 67%
“…To investigate how the amount 2 Iron per protein is in the form of iron(III) bound per protein rather than iron(II) added per protein, because not all of the added iron is assimilated into the protein core. 3 A340nm traces resulting from the autoxidation of iron(II) are complex, presumably due to a dependence of the rate on the presence of precipitated iron(III) mineral.…”
Section: Resultsmentioning
confidence: 99%
“…tularensis . Increasing global temperatures may allow for higher quantities of both mosquitoes and nectar-bearing flowers to exist seasonally due to more favorable growth conditions [34, 35]. Therefore, mosquito-borne tularemia, which is largely dependent upon weather patterns, may present an increased abundance in years to come.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Fe storage function of E. coli bacterial ferritin (EcFtnA) has been demonstrated both in vitro 31 and in vivo . 32 Amino-acid sequence comparisons and X-ray crystallographic studies 9,33 showed that EcFtnA contains a substrate Fe binding site that is homologous to the diiron binding ferroxidase center of H-type ferritins (sites A and B ). And, intriguingly, the X-ray crystallographic studies of EcFtnA 7,9,33 further revealed the presence of a third Fe binding site (site C ) in the vicinity of the H-type diiron ferroxidase center.…”
mentioning
confidence: 99%